Dynamic monitoring of high-performance distributed applications - Gunter, D.; Tierney, B.; Jackson, K.; Lee, J.; Stoufer, M. (11th International Symposium on High-Performance Distributed Computing (HPDC-11 2002), 2002)
Developers and users of high-performance distributed systems often observe performance problems such as unexpectedly low throughput or high latency. Determining the source of the performance problems requires detailed end-to-end instrumentation of all components, including the applications, operating systems, hosts, and networks. However, one must be very careful to design the instrumentation to have extremely low overhead, and not affect the system being monitored. In this paper we present a very light-weight instrumentation system that can be dynamically activated to unobtrusively collect and aggregate detailed end-to-end monitoring information from distributed applications. We also show how emerging "web services" can be used to facilitate remote interaction with this system.